Estimativa populacional e estado de saúde do boto-cinza, Sotalia guianensis (Van Beneden, 1864), no litoral de Fortaleza, Ceará, Brasil - Oliveira, Cinthya Leite de (2024)
The Guiana dolphin (Sotalia guianensis) is the aquatic mammal with the highest mortality rate along the coast of the state of Ceará, due to various anthropogenic impacts. The capital, Fortaleza, hosts one of the smallest populations of the species in the country, with 39 individuals monitored since the 1990s. Understanding the population dynamics and health conditions of these dolphins is essential to support conservation efforts and mitigate impacts. This study aimed to assess the population size and health status of Guiana dolphins in the coastal area of Fortaleza. The method used was mark-recapture through photo-identification. Data collection took place during 48 boat expeditions between October 2019 and December 2022, covering a total distance of 896.50 km, 189 hours of total effort, and 7539 photographs for animal identification and health assessment. Dolphins were found in 95.83% of the samples (n=46), with 59 hours of effective effort (31%). A total of 144 sightings were recorded, characterized by solitary animals to groups of 10 individuals (4.46 ± 2.1). Photo-identification of permanent marks on the dorsal fin enabled the diagnosis of 44 Guiana dolphins, with at least eight animals previously recorded in an identification catalog for the region. The population estimate was 61 individuals (SD±12.37; CV13%; 95% CI: 51-87). The health condition of 39 individuals was assessed, with 51.28% (n=20) in good body condition, followed by 48.72% (n=19) of individuals being thin and emaciated. Regarding injuries, 46.15% (n=18) presented traumatic lesions and 48.72% (n=19) had skin abnormalities. Traumatic lesions included trauma (10.26%; n=4), deformities in the dorsal fin (5.13%; n=2), and indeterminate marks (30.77%; n=12). Skin abnormalities were characterized by nodules (2.56%; n=1), whitish body spots (25.64%; n=10), abnormal pigmentation (5.13%; n=2), and lesions like “tattoo skin disease” (15.38%; n=6). The results indicate a significant increase in the population abundance of Guiana dolphins in the region compared to previous studies. However, the population also serves as an important bioindicator of coastal environmental quality, given the percentage of individuals in poor health. Therefore, the importance of a continuous monitoring program for the species in the region, which is considered a Natural Heritage of the Municipality of Fortaleza, is emphasized.